Implementasi Kebijakan Elektronik Online Pelayanan Kependudukan (E-Open) - Benedicta Gaby Andriana; Ananta Prathama (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This study aims to look at the implementation of the E-Open policy at the Bekasi City Population and Civil Registry Service using the George Edward III Implementation in which there are 4 indicators, namely communication, resources, disposition, and bureaucratic structure. The research method used is a qualitative method. The results of this research explain that the implementation of the E-Open policy has gone well, seen from the following indicators: 1) Communication: the information conveyed to the public regarding E-Open has been conveyed clearly. 2) Resources: human resources, information and facilities provided support the implementation of E-Open although they still need improvement. 3) Disposition: employees already have good commitment and ability and understand E- Open but lack the speed of response in responding to problems. 4) Bureaucratic structure: in the implementation of E-Open there are SOPs and distribution of responsibilities according to applicable regulations.